Compatibility between stimulated eye, target location and response location - Schankin, Andrea; Valle-Inclán, Fernando; Hackley, Steven A. (Psychological research, 2010)
Responses to stimuli are faster when the stimulus location spatially corresponds to the required response (standard Simon effect). Recently, a similar effect has been observed with monocular stimuli. Responses were faster when the response location and the stimulated eye corresponded (monocular Simon effect). It has been suggested that distinct mechanisms may underlie these two Simon effects. Here, we attempted to study these two mechanisms simultaneously. For mean reaction time, a finding of perfect additivity was obtained. These behavioral data coupled with surface electrophysiological measures support the view that two different mechanisms contribute independently to the monocular and standard Simon effect.